Kaldor's 1970 Regional Growth Model Revisited - A. P. Thirlwall (University of Kent, School of Economics, 2013)
Kaldor's 1970 paper 'The Case for Regional Policies' was republished in the sixtieth anniversary volume of the Scottish Journal of Political Economy. This paper reflects on the model after more than forty years, and argues that even though it has been criticised for its deterministic nature, it has lost none of its relevance. It predates the ideas of so-called 'new' growth theory, and the new economic geography of Krugman, and provides at least a partial explanation of why growth rates and levels of per capita income between regions and between countries can continue to persist and even widen in contrast to the predictions of orthodox equilibrium theory.
Keywords: O18; R11; 330; Regional Growth; Kaldor; Uneven Development; Cumulative Causation